A metal hydride air-conditioning system for fuel cell vehicles – Performance investigations. (15th December 2019) - Weckerle, C.; Nasri, M.; Hegner, R.; Linder, M.; Bürger, I.
Highlights: Detailed analysis of novel MH cooling system driven by compression work. Alternately operating MH reactors coupled to a PEM fuel cell. Influence of varied electrical FC powers and operating temperatures. Maximum cooling power of 807 W at an electrical power of 7 kW. Recommendations for improving the system performance. Abstract: An open cooling system based on metal hydrides is a promising new technology to reutilize the compression work in a hydrogen pressure tank by generating heat or cold. Our first of its kind system consists of two alternately operating plate reactors, which are filled with around 1.5 kg of Hydralloy C2 ( T i 0.98 Z r 0.02 V 0.41 F e 0.09 C r 0.05 M n 1.46 ) and coupled to a polymer electrolyte membrane fuel cell. In the present study, an extensive performance investigation for a variation of the main influencing parameters is performed: The electrical fuel cell power and the operating temperatures. Overall, it can be observed that in the entire range of various operating conditions, the fuel cell operation is not affected by the alternately operating H2 desorbing reactors. The variation of the electrical fuel cell power between 1.8 and 7.9 kW results in a maximum average cooling power of 807 W at an electrical power of 7 kW, reaching a specific cooling power of 276 W k g M H - 1 . The systems performance decreases with rising ambient temperatures (varied in the range: 24.3–42.3 °C) and decreasing cooling temperatures (varied in the range: 13–25.4 °C) due to increased thermal losses and reduced half-cycle times. Concluding the parameter variations, optimization recommendations are given and the expected performance for an improved system design is derived.